A double S shape provides the structural basis for the extraordinary binding specificity of Dscam isoforms. - Sawaya, M.R.; Wojtowicz, W.M.; Andre, I.; Qian, B.; Wu, W.; Baker, D.; Eisenberg, D.; Zipursky, S.L. (Cell, 2008)
Drosophila Dscam encodes a vast family of immunoglobulin (Ig)-containing proteins that exhibit isoform-specific homophilic binding. This diversity is essential for cell recognition events required for wiring the brain. Each isoform binds to itself but rarely to other isoforms. Specificity is determined by "matching" of three variable Ig domains within an approximately 220 kD ectodomain. Here, we present the structure of the homophilic binding region of Dscam, comprising the eight N-terminal Ig domains (Dscam(1-8)). Dscam(1-8) forms a symmetric homodimer of S-shaped molecules. This conformation, comprising two reverse turns, allows each pair of the three variable domains to "match" in an antiparallel fashion. Structural, genetic, and biochemical studies demonstrate that, in addition to variable domain "matching," intramolecular interactions between constant domains promote homophilic binding. These studies provide insight into how "matching" at all three pairs of variable domains in Dscam mediates isoform-specific recognition.